2019
DOI: 10.1155/2019/1651724
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus: Pathogenesis at the Functional Limit of Redox Homeostasis

Abstract: Systemic lupus erythematosus (SLE) is a disease characterized by the production of autoreactive antibodies and cytokines, which are thought to have a major role in disease activity and progression. Immune system exposure to excessive amounts of autoantigens that are not efficiently removed is reported to play a significant role in the generation of autoantibodies and the pathogenesis of SLE. While several mechanisms of cell death-based autoantigenic exposure and compromised autoantigen removal have been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 130 publications
0
22
0
Order By: Relevance
“…Increased mitochondrial ROS production and higher levels of O 2 - , H 2 O 2 , and HO • in SLE neutrophils ( 76 , 77 ) are met by a decreased redox capacity compared to healthy controls ( 68 , 251 , 254 ). This is due to lower concentrations of glutathione which is critical for adequate redox capacity ( 255 , 256 ). Neutrophils have a large capacity to keep glutathione in the reduced form via the activity of glutathione reductase (GRs) ( 257 ).…”
Section: Immunometabolismmentioning
confidence: 99%
“…Increased mitochondrial ROS production and higher levels of O 2 - , H 2 O 2 , and HO • in SLE neutrophils ( 76 , 77 ) are met by a decreased redox capacity compared to healthy controls ( 68 , 251 , 254 ). This is due to lower concentrations of glutathione which is critical for adequate redox capacity ( 255 , 256 ). Neutrophils have a large capacity to keep glutathione in the reduced form via the activity of glutathione reductase (GRs) ( 257 ).…”
Section: Immunometabolismmentioning
confidence: 99%
“…The SLE susceptibility genes that have been identified to date affect activation of autoimmune responses, resulting in aggregation of immune complexes [5]. Research also has found increased apoptosis and impaired phagocytosis in blood mononuclear cells of SLE patients [6,7].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…All these factors are implicated in the pathogenesis of systemic lupus erythematosus. 3 Patients with systemic sclerosis express high levels of exhaled hydrogen peroxide which may indicate oxidative stress in the airways. 4 Vitiligo and halo nevus Elevated hydrogen peroxide was found in both serum and lesional skin of vitiligo patients.…”
Section: Autoimmune Connective Tissue Diseasesmentioning
confidence: 99%